2005
DOI: 10.1104/pp.105.069732
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization and Light-Regulated Expression of Protoporphyrinogen IX Oxidase and Ferrochelatase in Chlamydomonas reinhardtii

Abstract: Protoporphyrinogen IX oxidase (PPO) catalyzes the last common step in chlorophyll and heme synthesis, and ferrochelatase (FeC) catalyzes the last step of the heme synthesis pathway. In plants, each of these two enzymes is encoded by two or more genes, and the enzymes have been reported to be located in the chloroplasts or in the mitochondria. We report that in the green alga Chlamydomonas reinhardtii, PPO and FeC are each encoded by a single gene. Phylogenetic analysis indicates that C. reinhardtii PPO and FeC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 68 publications
(76 reference statements)
3
49
0
Order By: Relevance
“…Previous studies have shown that, in plants, cryptochromes and ferrochelatase protect cells from high light intensity and are regulated by light, at least at the mRNA level [47,48]. In C. reinhardtii, the ferrochelatase content is higher in cells grown in continuous light than those grown in the dark [41], consistent with our results. Chaperone Hsps have been found in dinoflagellates and have been shown to be upregulated in proportion to the severity of the stress encountered [18,49].…”
Section: Differential Protein Expression Patterns Of a Catenella Undsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies have shown that, in plants, cryptochromes and ferrochelatase protect cells from high light intensity and are regulated by light, at least at the mRNA level [47,48]. In C. reinhardtii, the ferrochelatase content is higher in cells grown in continuous light than those grown in the dark [41], consistent with our results. Chaperone Hsps have been found in dinoflagellates and have been shown to be upregulated in proportion to the severity of the stress encountered [18,49].…”
Section: Differential Protein Expression Patterns Of a Catenella Undsupporting
confidence: 82%
“…Heme is also a cofactor in some component of the mitochondrial electron transport chain and in various nonchloroplast hemoproteins (for example, the catalases and peroxidases). In the green algae Chlamydomonas reinhardtii, the level of ferrochelatase in the cells is synchronized to the light/dark cycle and shows no significant variation with the phase of the cycle [41]. In A. catenella, the highest cryptochrome and ferrochelatase expressions were detected in the exponential phase, indicating that the highly light-regulated physiological activities (photosynthesis, signal transduction and biosynthesis) occurred in the exponential growth phase of the cells.…”
Section: Differential Protein Expression Patterns In a Catenella Durmentioning
confidence: 89%
“…These data indicate that PPO isoforms have dual localizations in both plastids and mitochondria in higher plants. However, only a single gene encoding PPO is present in a green alga (Chlamydomonas reinhardtii), the product of which is exclusively found in plastids (van Lis et al 2005). In the future, it will be important to clarify the physiological function of the PPO2 subfamily whose distribution is restricted in land plants.…”
Section: Intracellular Localization Of Enzymesmentioning
confidence: 99%
“…More recently, Woodson et al (2011) showed that in Arabidopsis FC1 and FC2 are co-localized within plastids. In C. reinhardtii, only a single gene encoding FeCh is present, the product of which is exclusively found in plastids (van Lis et al 2005). Obornik and Green (2005) performed the phylogenetic analysis of genes involved in heme biosynthesis in eukaryotes.…”
Section: Intracellular Localization Of Enzymesmentioning
confidence: 99%
“…Organelle Isolation and Partial Purification of Chloroplast ADHE-Isolation of chloroplasts and mitochondria from mutant strain 10-6C was essentially as described in (60). For the ADHE partial purification, the chloroplasts were resuspended in 50 mM HEPES (pH 7.0) in presence of protease inhibitors (0.5 mM benzamidine and 1 mM aminocaproic acid) to a final protein concentration of 5 mG/ml, frozen and thawed twice, and centrifuged at 11,000 Ď« g for 15 min at 4°C.…”
Section: Reinhardtii Strains Media and Culture Conditions-mentioning
confidence: 99%